A stress-based shear fracture criterion considering the effect of stress triaxiality and Lode parameter - Lou, Yanshan; Wu, Pengfei; Zhang, Chong; Wang, Jizhen; Li, Xvyang; Chai, Rugang; Yoon, Jeong Whan (International journal of solids and structures, 2022)
•A stress-based shear ductile fracture criterion is proposed to improve the prediction accuracy of failure for lightweight metals.•The mechanical behavior of AA5182-O sheet is uncovered from tension to equibiaxial tension.•The direct and inverse engineering methods are adopted to calibrate the fracture parameters.•The stress state-related fracture behavior of AA5182-O is numerically simulated.•The fracture limits of AA2024-T351 alloy from compression to tension is described by the sDF2016 criterion. Failure in lightweight metal forming is a big challenge currently and prevents their widely application in weight reduction of automobile and aerospace structures. A stress-based shear ductile fracture criterion is introduced in this study to improve the prediction accuracy of failure for lightweight metals. The criterion (sDF2016) is developed based on the DF2016 criterion thereby endowing the criterion with the precise fracture predictability under wide stress states of shear, uniaxial tension, plane strain tension and equibiaxial tension. Besides, the criterion takes into account the stress state effect on fracture in a form of the stress triaxiality, the maximum shear stress and the Lode parameter. The sDF2016 criterion is also expected to be less sensitive to strain path changing effect because sDF2016 describe the onset of fracture in stress space. For the verification of the proposed sDF2016 criterion, the experiments are carried out for AA5182-O sheet with central hole, notched, in-plane shear and bulging specimens. Plastic deformation is accurately modeled by the Swift-Voce hardening law and the Drucker yield function. The sDF2016 criterion is then calibrated both by the direct and inverse engineering approaches, which is applied to predict fracture initiation under distinct stress states. The modeled result indicates that the calibrated sDF2016 criterion based on the inverse engineering method predicts the fracture stroke with a higher accuracy than the direct approach. The sDF2016 criterion is also used to depict fracture limits of AA2024-T351 alloy from compression to tension. The application shows that the proposed ductile fracture criterion is capable of modeling the fracture limits for sheet metals under various loading conditions from shear to plane strain tension.